Molecular Characterization of Escherichia Coli Serotype 0157:H7 Utilising Contemporary PCR Techniques and PFGE-Genotyping - Ooi, Wai Ling (2000)
A total of 28 strains of Escherichia coli 0157:H7 which were originally isolated from beef and chicken samples from various locations in Malaysia were examined and further characterized by various molecular techniques. These techniques include the plasmid profiling, antibiotic resistance, multiplex PeR, RAPD pattern, PFGE, and also ERIC fingerprinting. All the strains utilized in this study were found to exhibit a multiple antibiotics resistance pattern to the fourteen antibiotics [ bacitracin (100%), penicillin G (100%), sulphafurazole (82%), ampicillin (61%), cephalothin (57%), carbenicillin (50%), ceftazidime (39%), erythromycin (32%), streptomycin (18%), nalidixic acid (14%), chloramphenicol (11%), kanamycin (7%), latamoxef (7%), and tetracycline (7%)] used. The plasmid profile obtained ranged in sizes from 3.23 MDa to 60 MDa. Development of a PCR identification assay for Escherichia coli 0157:H7 is based on the isolation of species-specific DNA. Two types of specific primer encoding the Shiga-Like Toxin gene, the SLnI (584 bp) gene and SLn (348 bp) were utilized in the multiplex PCR assay. Analysis carried out demonstrated that Escherichia coli 0157:H7 strains were positive for the presence of single SLm gene (17.9 %) or both the SLlI and SLlII genes (82.1%). Three 50% G+C contents 10-mer random primers, the Gen 1-50-01 (5'-GTGCAATGAG-3'), Gen 1-50-06 (5'-AGGTTCTAGC-3'), and Gen 1-50-09 (5'-AGAAGCGATG-3') were chosen after screening through ten random primers. In PFGE technique carried out, two kinds of restriction enzymes, the SpeI (5'-A-l,CTAGT-3') and XbaI (5'T -l,CTAGA-3') were used to check for the in-situ DNA digestion pattern due to their inherit advantages of the short sequence of these enzymes. Both the RAPD polymorphism pattern and the PFGE profile obtained showed a significant discriminatory fingerprinting among the 28 isolates under studied. A respective dendrogram was constructed from the binary data matrix obtained from the RAPD, PFGE and ERIC fingerprints to compare the diversity relationship among the 28 isolates. All the dendrograms were constructed utilising the RAPDistance software package based on the data retrieved from the presence or absence of banding pattern. ERIC genotyping technique was used as an additional molecular typing method to further assists in the molecular characterization of the Escherichia coli 0157:H7. Interestingly, all the three molecular techniques of RAPD, PFGE, and ERIC genotyping showed a significant correlation whereby the first 14 and the second 14 isolates of Escherichia coli 0157:H7 used in this study showed a closer relationship in the respective cluster groups as shown in the constructed dendrograms. From the overall results obtained both the RAPD and PFGE analysis showed greater discriminatory power compared to the other phenotypic and molecular characterization techniques used in this study. Our results demonstrate that the plasmid profiling, multiplex PCR, RAPD-PCR fingerprinting, PFGE and ERIC profiling methods are able to act as one of the most appropriate and suitable analysistools for a rapid and reliable molecular typing and identification of Escherichia coli 0157:H7.